Fake and Real Massaging at the Same Time with QR Code in Web Services for Different Users - Yesiltepe, Mirsat; Kurulay, Muhammet (WILEY-HINDAWI, 2018)
At present, the notion of a cloud has expanded so much that there is no area of knowledge other than the concept of cloud. The most important reason for this is the ambiguity in the definition of this concept in the literature. Some have used the concept of a mobile cloud to create private cloud environments, while others have defined the cloud as a complex environment consisting of many different entities and layers, while others regard the cloud as parallel, discrete, and grid. In other words, the concept of cloud can sometimes be limited by the user devices and sometimes by the user devices. QR code, which is a precise and accurate way of communicating a text or symbol to the other side, is very broad, as is the concept of cloud use. The use of this technology is increasing with the availability of data encryption algorithms. As an abbreviation of the term QR code, the QR phrase Quick Response, which is the English language name, is used. In this study, when the same request is requested for different users (clients) in the web service, the response generated by the server at one time is sent to the different users at one time and the users get different messages. It is intended to reduce the load on the server and respond more efficiently to clients. Scrambled steganographic QR codes will be used for these operations. Some of the highlights of the paper are different message transmission with the same QR code to different users in web services and message verification with a hash value, using fake keys and advantage of changeable security mechanism.
Keywords: IMAGE; AUTHENTICATION; ENCRYPTION; SCHEME; Computer Science; Telecommunications